Chronological developments in the Old Kingdom tombs in the necropoleis of Giza, Saqqara and Abusir : toward an economic decline during the early dynastic period and the Old Kingdom - Roeten, Leo (Archaeopress Egyptology, 2016)
This study suggests, through investigations of the tombs in the necropolis of Giza, that economic decline attributed to the collapse of the Old Kingdom had already started in the early dynastic period.